P-111 Using Stiffness Imaging of the Intestine to Predict Response to Medical Therapy in Obstructive Crohn's Disease. (March 2016) - Stidham, Ryan; Dillman, Jonathan; Rubin, Jonathan; Higgins, Peter
Abstract : Background: Intestinal fibrosis continues to present a significant hurdle in the management of Crohn's disease. Repeated episodes of inflammation and abnormal wound healing result in progressive intestinal fibrosis, strictures, and bowel obstruction. While inflammatory Crohn's disease often responds to medical therapy, predominantly fibrostenotic intestinal disease is unresponsive. Our inability to accurately distinguish intestinal inflammation from fibrosis frequently leads to futile trials of therapeutics delaying inevitable surgery, and unnecessarily exposing the patient to the risks of steroids and immunosuppression. Measures of fibrotic burden could improve the ability to predict whether disease is responsive to medical therapy or instead is destined for surgery in the short term. Methods: Patients hospitalized for abdominal pain with Crohn's disease involving the ileum, small bowel dilation of >3.5 cm, no penetrating features, who were started on methylprednisone, were enrolled for ultrasound study. Subjects underwent bedside ultrasound scan of diseased appearing intestine using Siemens Acuson S3000 and quantitative acoustic radiation force impulse (Siemens, USA). Scans of diseased bowel were preformed within 24 hours of methylprednisone initiation and again 3 days following the baseline scan. Shear wave velocity measurements (SWV) were collected at applied strains of 0% and 10%. Demographics, body mass index (BMI), medical history, and Harvey-Bradshaw index (HBI) were measured. The primary outcome was surgical resection of disease bowel within 90 days of hospital discharge. Results: Twenty-eight subjects completed follow up with 9/28 undergoing surgical bowel resection within 90 days. Patient demographic features, BMI, CRP, anti-TNF and immunomodulator use did not significantly differ between surgical and non-surgical groups. Baseline mean SWV without use of freehand force (0% strain) did not discriminate those requiring surgery within 90 days, with SWV of 1.52 m/s ± 0.096 versus 1.44 m/s ± 1.268, P = 0.238. With the application of 10% freehand strain to the affected segment, baseline SWV were faster in those undergoing surgical resection, though the difference was not statistically significant, 2.02 m/s ± 0.291 versus 1.88 m/s ± 0.254, P = 0.128. No significant difference in SWV change between baseline and day 3 was observed between the surgical and non-surgical groups. Conclusions: ARFI elastography imaging was unable to demonstrate a statistically significant difference in stiffness values between those with medical responsive and non-responsive stricturing Crohn's disease. Expected limitations of ultrasound remain barriers including body habitus and challenges consistently identifying the same loop of bowel for interrogation. However, as the technology continues to improve, including clinical use of contrast enhanced ultrasound and low cost high frequency transducers, ultrasound and stiffness imaging may yet prove to provide non-invasive bedside disease characterization and quantitation of activity.